1998
DOI: 10.1101/gad.12.14.2175
|View full text |Cite
|
Sign up to set email alerts
|

EIR1, a root-specific protein involved in auxin transport, is required for gravitropism inArabidopsis thaliana

Abstract: The EIR1 gene of Arabidopsis is a member of a family of plant genes with similarities to bacterial membrane transporters. This gene is expressed only in the root, which is consistent with the phenotypes of the eir1 mutants-the roots are agravitropic and have a reduced sensitivity to ethylene. The roots of eir1 mutants are also insensitive to the excess auxin produced by alf1-1 and fail to induce an auxin-inducible gene in the expansion zone. Although they fail to respond to internally generated auxin, they res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
726
1
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 768 publications
(756 citation statements)
references
References 49 publications
19
726
1
10
Order By: Relevance
“…The distribution of auxin depends on both auxin metabolism (biosynthesis, conjugation and degradation) [8][9][10] and cellular auxin transport [11][12][13][14][15] . We identified in silico a novel putative auxin transport facilitator family, called PIN-LIKES (PILS).…”
mentioning
confidence: 99%
“…The distribution of auxin depends on both auxin metabolism (biosynthesis, conjugation and degradation) [8][9][10] and cellular auxin transport [11][12][13][14][15] . We identified in silico a novel putative auxin transport facilitator family, called PIN-LIKES (PILS).…”
mentioning
confidence: 99%
“…Brassica juncea and tobacco plants were grown in the green house with a 12 h light (26 ) and 12 h dark (20 ) period. Arabidopsis plants were grown in a phytotron in soil with a 16 h light (22 ) and 8 h dark (15 ) period. [29].…”
Section: Bacteria and Plantsmentioning
confidence: 99%
“…Further proof of AUX1 as an auxin influx carrier was provided by the work of Yamamoto and Yamamoto (1998) [19]. A breakthrough in the study of polar auxin transport has been marked with the cloning of two genes, Atpin1 and Atpin2, which encoded presumptive auxin efflux carriers [20][21][22][23][24]. Pin-formed inflorescence and decreased polar auxin transport activity of the Arabidopsis pin1 mutant indicated that the primary function of the AtPIN1 protein was for polar auxin transport in the inflorescence axis [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations